Kajian Prospek Pemanfaatan Zeolit pada Industri Kertas - Lies Indriati; Jenni Rismijana (JURNAL SELULOSA, 2005)
The Review on Prospect of Zeolite Utilization in Paper Industry AbstractZeolite is one of natural mineral which can be used as an additive in papermaking process; i.e. as paper filler, coating pigment, stickies control agent, etc. The utilization of zeolite as filler for paper has been developed. It has been produced commercially in Japan. In Indonesia, its usage in papermaking process has not been developed yet. A laboratory scale investigation of zeolite utilization as paper filler has been carried out. The zeolit used was not meet the requirements as paper filler. It was caused by a large content of impurities in zeolite used, aswell as its silica content. Mechanical process in production of zeolite as paper filler is not enough to meet therequirements of paper filler.Another usage of zeolite in papermaking process has been investigated. The result showed that zeolite canbe used as a stickies control agent in waste paper recycling. It reduces dirt count while increases the brightnessof paper produced.This potential should be developed further since there is a large availability of zeolite in Indonesia and anumber of paper industries which can utilize zeolite in their papermaking process.Key words : zeolite, utilization, additive, filler, papermaking AbstrakZeolit merupakan mineral alam yang dapat digunakan sebagai bahan penolong pada proses pembuatan kertas, diantaranya sebagai bahan pengisi kertas, pigmen salut, bahan pengendali sticky (pengotor yang bersifat lengket) pada kertas bekas. Penggunaan zeolit sebagai bahan pengisi kertas telah dikembangkan di beberapa negara. Di Jepang, bahan pengisi dari zeolit telah diproduksi secara komersial, di China telah diteliti dan diupayakan pemanfaatannya. Sementara di Indonesia, penggunaannya pada proses pembuatan kertasmasih dalam penelitian dan pemanfaatannya di industri kertas belum dikembangkan. Hasil penelitian skala laboratorium yang dilakukan telah menunjukkan bahwa penggunaan zeolit sebagaibahan pengisi kertas belum memenuhi syarat. Hal ini disebabkan oleh kandungan bahan pengotor dan silikadalam zeolit alam cukup tinggi sehingga masih perlu pengolahan sebelum dimanfaatkan. Namun pada penggunaan zeolit sebagai bahan pengendali stickies, hasil penelitian menunjukkan potensinya yang prospektif menurunkan jumlah noda dan meningkatkan derajat putih kertasPotensi zeolit tersebut di atas perlu dikembangkan potensinya dan diaplikasikan lebih lanjut mengingat ketersediaan zeolit yang cukup tinggi di Indonesia dan banyaknya industri kertas yang dapat memanfaatkan zeolit pada proses pembuatan kertasnya Kata kunci : Zeolit, pemanfaatan, aditif, bahan pengisi, pembuatan kertas